The abundance-capacity fraction: A simple indicator for peak abundance timing of Culex mosquitoes - Kollas, Nikos; Angelou, Anastasia; Mourelatos, Spiros; Stilianakis, Nikolaos I.; Kioutsioukis, Ioannis (Ecological Informatics, 2026)
Abundance models that correctly describe the seasonal dynamics of mosquito populations are crucial in the study of mosquito borne diseases such as Zika, malaria, chikungunya and West Nile Virus disease. Taking into consideration experimental results for the mortality rate of mosquitoes in reproductive diapause and the distinct response of diapause termination and induction with respect to day-length, we update the entomological compartment of a commonly used West Nile virus transmission model. We observe that the fraction of adult mosquito abundance at the beginning of the year with respect to the carrying capacity of larvae is monotonically related to the date at which adult abundances peak, with small values corresponding to peak in abundances late in the year and larger values earlier on. We use the model to infer the value of the carrying capacity from experimental data for the administrative region of Central Macedonia in Northern Greece from 2011 to 2023 and demonstrate its effectiveness in capturing monthly averages of mosquito abundances, the variability in observed peak dates and the evolution of population dynamics over an entire season at the municipal level.
CRIS-Team Scopus Importer:2025-12-19
Keywords: Diapause; Mosquito abundance model; Non-diapausing fraction; Northern Greece; West Nile virus